Evaluation of a Gadolinium-Based Nanoparticle (AGuIX) for Contrast-Enhanced MRI of the Liver in a Rat Model of Hepatic Colorectal Cancer Metastases at 9.4 Tesla - Fries, P.; Morr, D.; Müller, A.; Lux, F.; Tillement, O.; Massmann, A.; Seidel, R.; Schäfer, T.; Menger, M. D.; Schneider, G.; Bücker, A. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2015)
Purpose: The aim of this study was to compare a Gd-based nanoparticle (AGuIX) with a standard extracellular Gd-based contrast agent (Gd-DOTA) for MRI at 9.4 T in rats with hepatic colorectal cancer metastases.Materials and Methods: 12 rats with hepatic metastases were subjected to MRI using a 9.4 T animal scanner. T1w self-gated FLASH sequences (TR/TE = 45/2.5 ms, alpha = 45°, TA = 1: 23 min, FOV = 5.12 × 5.12 cm2, matrix = 256 × 256) were acquired before and at 10 time points after contrast injection. Each animal received 0.1 mmol/kg BW Gd-DOTA i. v. 2 days later AGuIX was applied at 0.01 mmol/kg BW (representing equal Gd doses). The SNR of normal liver (SNRliver), hyper- and hypoenhancing parts of tumors (SNRtumor, hyperenh/SNRtumor, hypoenhanc), erector spinae muscle (SNRmuscle), CNR and lesion enhancement (LE) were calculated based on ROI measurements.Results: Mean SNRliver (Gd-DOTA: 14.6 +/–0.7; AGuIX: 28.2 +/–2.6, p < 0.001), SNRtumor, hyperenhanc (Gd-DOTA: 18.6 +/–1.2; AGuIX: 29.6 +/–2.8, p < 0.001), SNRtumor, hypoenhanc (Gd-DOTA: 12.0 +/–0.7; AGuIX: 15.4 +/–0.7, p < 0.001), SNRmuscle (Gd-DOTA: 12.3 +/–0.3; AGuIX: 14.0 +/–0.7, p < 0.001), mean CNR (Gd-DOTA: –2.5 +/–0.2; AGuIX: –7.5 +/–1.0, p < 0.001) and LE (Gd-DOTA: 3.8 +/–0.7; AGuIX: 14.9 +/–2.8, p = 0.001) were significantly higher using AGuIX. Regardless of the larger molecular size, AGuIX demonstrates an early peak enhancement followed by a continuous washout.Conclusion: AGuIX provides better enhancement at 9.4 T compared to Gd-DOTA for equal doses of applied Gd. This is based on the molecule structure and the subsequent increased interaction with protons leading to a higher relaxivity. AGuIX potentially ameliorates the conspicuity of focal liver lesions and may improve the sensitivity in diagnostic imaging of malignant hepatic tumors.Key Points:• AGuIX provides superior enhancement as compared to the extracellular compound Gd-DOTA at 9.4 T.• AGuIX may improve the detection and diagnostic sensitivity of malignant focal liver lesions.• The small size of AGuIX allows for fast renal clearance and prevents undesirable accumulation in the body.Citation Format: • Fries P, Morr D, Müller A et al. Evaluation of a Gadolinium-Based Nanoparticle (AGuIX) for Contrast-Enhanced MRI of the Liver in a Rat Model of Hepatic Colorectal Cancer Metastases at 9.4 Tesla. Fortschr Röntgenstr 2015; 187: 1108 – 1115
Keywords: MR imaging; abdomen; metastases; contrast agents; gadolinium; experimental study